Did Soviet Elderly Employment Respond to Financial Incentives? Evidence from Pension Reforms - Olga Malkova (Institute of Labor Economics (IZA), 2019)
This study answers the open question of whether workers respond to financial incentives in a command economy. To do this, I evaluate pension reforms in Soviet Russia in 1964 and 1969 that allowed pensioners to receive a greater share of their pensions if they worked, resulting in a progressive elimination of benefit reduction rates. Variation in group eligibility and variation in benefit reduction rates in eastern and western regions allow for the use of several difference-in-differences frameworks. I collect and digitize novel data from the Soviet archives on pensioner employment, constructing the first database of the Soviet old-age labor market. I find that Soviet pensioners are responsive to financial incentives. By 1969, after the benefit reduction rate fell from an average of 47.8 to 24.1 percent, pensioner employment rates rose by 5.7 percentage points, representing a 47 percent increase. Finally, I provide illustrative estimates of the employment elasticity with respect to the average net-of-tax rate that range from 0.6 to 1.4.
Keywords: J18; J26; H55; 330; pension; retirement; employment; Soviet economy